2010
DOI: 10.1007/s10681-010-0300-2
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative trait loci associated with seed set under high temperature stress at the flowering stage in rice (Oryza sativa L.)

Abstract: High temperature stress (HTS), an increasingly important problem in rice production, significantly reduces rice yield by reducing seed set percentage (SSP). Breeding rice varieties with tolerance to HTS at the flowering stage is therefore essential for maintaining rice production as the climate continues to warm. In this study, two quantitative trait loci (QTL) underlying tolerance to HTS were identified using the recombinant inbred lines (RILs) derived from a cross between the HTS-tolerant rice cultivar 996 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
48
1
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(54 citation statements)
references
References 24 publications
(26 reference statements)
2
48
1
3
Order By: Relevance
“…Several QTLs have been mapped for heat tolerance at flowering stage (Ye et al 2011;Jagadish et al 2010a;Zhang et al 2008;Xiao et al 2011). In our study, RM250 and RM88 were associated with days to flowering in normal and poly cover house methods respectively but same type of alleles were observed in both susceptible and tolerant checks indicating they are not specific to a haplotype.…”
Section: Discussionmentioning
confidence: 43%
See 2 more Smart Citations
“…Several QTLs have been mapped for heat tolerance at flowering stage (Ye et al 2011;Jagadish et al 2010a;Zhang et al 2008;Xiao et al 2011). In our study, RM250 and RM88 were associated with days to flowering in normal and poly cover house methods respectively but same type of alleles were observed in both susceptible and tolerant checks indicating they are not specific to a haplotype.…”
Section: Discussionmentioning
confidence: 43%
“…Marri et al (2005) reported RM263 and RM183 on chromosome 2 linked to yield enhancing QTLs qyld 2.1 and qyld 2.2 and RM297 and RM223 to high spikelet number per panicle. Xiao et al (2011) reported two QTLs qPF4 and qPF6 between RM5687 and RM471 on chromosome 4 and between RM190 and RM225 on chromosome 6 respectively, affecting pollen fertility in RILs derived from a cross between a heat tolerant rice cultivar 996 and a sensitive cultivar 4628. However these markers were not associated with any trait in our study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some of the QTLs identified in different populations are overlapped or closely linked (Table 1). Among the identified QTLs, a QTL for spikelet fertility under high temperature, qHTSF4.1 from n22, was identified in different genetic backgrounds in different studies (Jagadish et al, 2010;Xiao et al, 2011;Ye et al, 2012Ye et al, , 2015a. To fine map and validate the effect of heat tolerance QTL qHTSF4.1, PCR-based SnP markers were developed and used to genotype BC 2 F 2 , BC 3 F 2 , BC 3 F 3 , and BC 5 F 2 populations from the cross combination of IR64/n22.…”
Section: Genetic Analyses For Hiss At Floweringmentioning
confidence: 99%
“…Cekaman suhu tinggi selama fase berbunga padi menyebabkan penurunan vigor serbuk sari, dan fertilitas spikelet (Prasad et al, 2006;Jagadish et al, 2011;Poli et al, 2013). Penurunan vigor serbuk sari dapat dianggap sebagai faktor fisiologi yang bertanggung jawab terhadap penurunan produksi gabah pada kondisi suhu tinggi (Tang et al, 2008;Zhang et al, 2008;Xiao et al, 2011).…”
unclassified